Circulating Nucleic Acids in Early Diagnosis, Prognosis and Treatment Monitoring An Introduction - Gahan, Peter B. (Advances in Predictive, Preventive and Personalised Medicine,, 2015)
DNA and RNA fractions can be isolated from a variety of body fluids including whole blood, serum, plasma, urine, saliva and cerebrospinal fluid from both patients and healthy individuals.  Such isolates can be exploited in the early detection of clinical disorders, stratification of patients for treatment, treatment monitoring and clinical follow-up.  In addition, the use in fetal medicine allows the early detection of fetal sex, Rh factor and aneuploid disorders as well as following both fetal and premature born infant development. This volume is intended as a primer for those who are interested in entering the field of circulating nucleic acids. The areas covered in this volume include: ·      Background and general biology of circulating nucleic acids ·      Methodology ·      Applications of circulating nucleic acids ·      Quality Assurance ·      Ethics.